UPAYA MENGEMBANGKAN BAHASA ANAK USIA DINI MELALUI MEDIA AUDIO VISUAL - Ninda Abellia; Meriatul Kibtiyah; Elfara Hajjar Sujani (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
This research is entitled efforts to develop early childhood language through audio-visual media. This research is a qualitative descriptive study with the object of research being 29 students at KB Rara whose address is Payakabung Village. This research uses primary data obtained through observation and interviews. The research results stated that after using audio-visual media in the learning process, children's language skills increased. Apart from that, the table also shows the results regarding the categories of children's language development in KB Rara, namely BB (Not Yet Developing) at 0%, MB (Starting to Develop) at 0%, BSH (Developing According to Expectations) at 82.8%, and BSB ( Developing Very Well) as much as 17.2%. Thus, it can be concluded that using audio-visual media learning methods in children's learning activities can improve children's language skills.